THE ROLE OF NEW TRANSPORT POLICY ON CREATING SUSTAINABLE AND INTEGRATED PUBLIC TRANSIT SYSTEM IN JAKARTA (Case Study: Transjakarta, Indonesia and Freiburg, Germany) - , MUCHLISIN; , Prof. Dr.-Ing. Ir. Ahmad Munawar, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Creating sustainable transport become an important key to maintain our environment. Sustainable development is one that meets the needs of the present without compromising the ability of future generations to meet their own needs. Transport policy also has the direct impact and indirect impact that affected to the travelers. Nowadays, Jakarta is facing major challenges in the integrating sustainable transport policy. Research methodology of this research is using qualitative research. By fitting between theories and data collection, qualitative research tends to be associated with words or images as the unit of analysis. The hypothesis was tested by spreading questioners to the respondents as primary data. Learning from successful history of Freiburg about sustainable transport development would make Jakarta understand what the really Jakarta needs to develop sustainable transport policy. This study explored three main groups of policies that can be used to mitigate negative environmental impacts of transport. There are transport technology, transport supply and transport demand. Thus, the result of improving new transport policies to create sustainable public transit are (1) implementing transport technology